Strategi Pemanfaatan Media Instagram sebagai Media Promosi Kuliner pada Akun @Kepdan_Kopi - Khairunnisa Ritonga; Abdul Rasyid (MUKASI: Jurnal Ilmu Komunikasi, 2025)
This study aims to examine the strategy of utilizing Instagram media as a culinary promotion medium on the @Kepdan_Kopi account. The background of this study is based on the rapid development of social media as a digital marketing tool, especially Instagram which has great potential in expanding the reach of culinary product promotion. This study aims to understand how the @Kepdan_Kopi account uses Instagram to increase its appeal and interaction with consumers. The method used is descriptive qualitative with data collection techniques through observation of @Kepdan_Kopi Instagram content, interviews with account managers, and documentation of promotional activities. Data analysis was carried out inductively by examining content patterns, communication strategies, and audience responses to describe in detail the promotional practices carried out. The results of the study show that the @Kepdan_Kopi account utilizes Instagram features such as stories, reels, and feeds creatively to build brand awareness and engagement. The strategies implemented include presenting attractive visuals, using persuasive captions, and actively interacting with followers to increase customer loyalty. This approach is effective in attracting attention and strengthening the image of the culinary product being promoted. In conclusion, Instagram is a strategic promotional media for culinary businesses such as @Kepdan_Kopi by utilizing digital features optimally. This study provides important insights for culinary business actors in developing adaptive and innovative digital marketing strategies.